2015
DOI: 10.1371/journal.pone.0125218
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of HIV and Prevention Needs of Men Who Have Sex with Men in Abidjan, Cote d’Ivoire

Abstract: To determine HIV prevalence and associated risk factors among men who have sex with men (MSM) in Abidjan, Côte d’Ivoire. We conducted a cross-sectional RDS survey of MSM in Abidjan from October 2011 to February 2012. Eligibility criteria included age ≥ 18 years and having had oral or anal sex with another man in the last 12 months. Weighted data analysis was conducted with RDSAT and SAS. We enrolled 603 participants, of whom 601 (99.7%) completed the questionnaire and 581 (96.7%) consented to HIV testing. HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 21 publications
7
44
1
Order By: Relevance
“…Most MSM from the Inner Mongolia Autonomous Region of China in our sample were between 23 and 35 years old; this finding is consistent with the survey results of Luo et al of 259 MSM in Hangzhou (74.5 %) [40] but inconsistent with those of Hakim et al, who found that 35.9 % of 603 MSM in Abidjan were between 23 and 35 years old [41]. …”
Section: Discussionsupporting
confidence: 89%
“…Most MSM from the Inner Mongolia Autonomous Region of China in our sample were between 23 and 35 years old; this finding is consistent with the survey results of Luo et al of 259 MSM in Hangzhou (74.5 %) [40] but inconsistent with those of Hakim et al, who found that 35.9 % of 603 MSM in Abidjan were between 23 and 35 years old [41]. …”
Section: Discussionsupporting
confidence: 89%
“…12,19,23,24,49,6567 Sandfort et al 21 found that men in South Africa who tested HIV-positive in the study were more likely to be categorized as hazardous drinkers as measured by the AUDIT than HIV-negative men (54.5% versus 40.0%; AOR: 1.81; 95%CI: 1.06, 3.07). Baral et al 68 reported that men in Swaziland who drank alcohol at least one day in the preceding month were not more likely to be HIV infected than other men (AOR based on weighted data: 2.18; CI95%: 0.60, 7.95).…”
Section: Resultsmentioning
confidence: 91%
“…Baral et al 68 reported that men in Swaziland who drank alcohol at least one day in the preceding month were not more likely to be HIV infected than other men (AOR based on weighted data: 2.18; CI95%: 0.60, 7.95). Hakim et al, 67 with a more sensitive measure, found that men who drank alcohol once a week or less and men who drank more than once a week were not more likely to be HIV positive compared to men who reported never using any alcohol (OR 0.89; 95%CI: 0.62, 1.28; and OR 1.12; 95%CI: 0.82,1.52, respectively). Sanders et al 16 reported HIV incidence among non-alcohol users incidence as 7.6 per 100 person years (PY; 95%CI: 5.0, 11.5) compared to 9.3 per 100 PY; 95%CI: 6.8, 12.5; unadjusted incidence rate ratio: 1.2; 95%CI: 0.7, 2.1) among men who had used any alcohol in the preceding month.…”
Section: Resultsmentioning
confidence: 99%
“…In sub-Saharan Africa, approximately 5% of the general population is living with HIV, compared to nearly 18% of men who have sex with men (Beyrer et al, 2012). This distribution is strikingly similar in Abidjan, where 5.1% of the general population is HIV+ (PEPFAR, 2013), while 18% of men who have sex with men in Abidjan are living with HIV (Aho et al, 2014, Hakim et al, 2015; Vuylsteke et al, 2012). However, this universalizing category of practice, which eschews identity in favor of behavior, erases a significant amount of heterogeneity.…”
Section: “Msm” Foreign Interventions and Sexual And Gender Minority mentioning
confidence: 88%
“…Though they did ask survey respondents whether or not they identified as travestis, only 2% of the sample identified as such, providing little evidence about how their experience might differ from that of gender normative branchés. Descriptive statistics of these categories were only presented in the original report (Semde-Abla 2012) but were ignored entirely in subsequent publications (Vuylsteke et al 2012; Aho et al 2013; Hakim et al 2015). Furthermore, questions posed about the gender of respondents' sex partners did not include travestis or transgender persons as an option, providing minimal information about the extent to which gender-normative men who have sex with men engage sexually with travesti and transgender partners.…”
Section: Branchés In Focus: the Language And Politics Of “Msm Health”mentioning
confidence: 99%